Interpersonal Trauma and Risk of Depression Among Adolescents: The Mediating and Moderating Effect of Interpersonal Relationship and Physical Exercise - Chen, Runsen; Peng, Ke; Liu, Jianbo; Wilson, Amanda; Wang, Yuanyuan; Wilkinon, Meredith R.; Wen, Siying; Cao, Xiaolan; Lu, Jianping (Frontiers in Psychiatry, 2020)
Adolescent interpersonal trauma is an important public health concern. Depression is the main consequence of interpersonal trauma, which consistently results in various negative mental health outcomes. Previous research has investigated the independent effects of interpersonal trauma, interpersonal relationship and physical exercise on risk of developing depression. However, the interaction effect of the three factors on depression remains unclear. We aim to investigate the risk factors for the development of depression in adolescents, and explore the interaction effect of the three aforementioned factors. A multistage sampling cross-sectional study was conducted in Shenzhen, China. A total of 1883 adolescent from 11 middle schools and high schools were recruited. Demographic information, depressive symptoms, physical exercise, interpersonal relationship, interpersonal trauma, and academic record were collected using standardized questionnaires. A linear regression model was performed to explore the association between variables and development of depression. Structural equation modeling was used to explore the role of potential mediators and moderators. The results showed that interpersonal trauma and poorer interpersonal relationships were significantly associated with the development of depression (p < 0.05). After adjusting for age, sex and academic record, physical exercise was found to be a significant predictor of depression (p < 0.05). We identified a mediating role of interpersonal relationships in the relationship between interpersonal trauma and depression, and a moderating role of physical exercise between interpersonal relationships and depression. This is the first study to provide the developing mechanism of depression in adolescents, which examined the interaction effects of interpersonal trauma, interpersonal relationships and physical exercise. The current study provides insights into factors which impact the mental health of adolescents. Through examining these factors one can gain insight into potential risk factors for developing depression and therefore then develop interventions in order to help adolescents.